2008
DOI: 10.1136/adc.2007.136036
|View full text |Cite
|
Sign up to set email alerts
|

A novel combined Hib-MenC-TT glycoconjugate vaccine as a booster dose for toddlers: a phase 3 open randomised controlled trial

Abstract: NCT00258700. Study ID: 103974 (http://clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
2
13
1
Order By: Relevance
“…The differences between vaccines in induction of MenC-specific memory B-cells may explain the differential antibody response noted following primary and booster vaccines when children were primed with either a MenC-CRM 197 vaccine or Hib-MenC-TT in the first year of life and given a Hib-MenC-TT booster as toddlers [8], [9]. In these earlier studies, children in the MenC-CRM 197 primed groups had higher SBA titres one month after primary vaccines, but lower SBA titres one month after the Hib-MenC-TT booster, than children in the Hib-MenC-TT primed groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences between vaccines in induction of MenC-specific memory B-cells may explain the differential antibody response noted following primary and booster vaccines when children were primed with either a MenC-CRM 197 vaccine or Hib-MenC-TT in the first year of life and given a Hib-MenC-TT booster as toddlers [8], [9]. In these earlier studies, children in the MenC-CRM 197 primed groups had higher SBA titres one month after primary vaccines, but lower SBA titres one month after the Hib-MenC-TT booster, than children in the Hib-MenC-TT primed groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of waning bactericidal antibody described in the first year of life following infant immunizations [8], [30], an increase in the number of MenC-specific memory B-cells between 5 and 12 months of age suggests that after primary MenC vaccines, memory B-cells continue to be generated for several months, but there is a decline in the proportion that differentiate into plasma cells. Despite waning of bactericidal antibody levels, antibody avidity has also been shown to increase following primary immunisations with MenC and pneumococcal conjugate vaccines in infants, until 12 months of age [11], [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient published data exist to determine whether carrier proteins have a meaningful impact on the clinical efficacy of meningococcal vaccines 49,70,71. A recent study in toddlers who received a booster dose of combined Haemophilus influenzae type B and meningococcal serogroup C vaccine employing a tetanus toxoid protein carrier indicated that boosting was superior among children primed with tetanus toxoid-containing vaccines 72,73. Similar studies have not been performed for CRM conjugate vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…these results are in line with previous studies showing that high anti-pRp concentrations are induced when Hib antigens are combined with Menctt antigens (eg, Hib-Menc-tt vaccine). [25][26][27][28] this suggests a potential positive interference of the Menc-tt antigen on the Hib response through their common carrier or by another mechanism. alternatively, the higher Hib response could be explained by a reduction of immune interferences that have been observed in Dtpa-Hib combination vaccines.…”
Section: Discussionmentioning
confidence: 95%